Role of a mobile/USB endoscope in dacryology - Hare Ram Ojha; Neha Verma; Arunima Gupta; Alka Tripathi (Indian Journal of Ophthalmology)
To establish the role of a mobile/Universal Serial Bus (USB) endoscope in dacryology. A prospective observational study was conducted at a tertiary ophthalmic institute. A mobile/USB endoscope comprising a 14 cm long camera probe, 5.5 mm in diameter, consisting of a 1.3 MP mini camera and six light-emitting diode adjustable lights, was used for performing nasal endoscopy and therapeutic/minor procedures. This study was divided into three parts: diagnostic, minor, and therapeutic procedures. For diagnostic purposes, nasal endoscopy was performed – preoperative (n = 31) and postoperative (n = 22) dacryocystorhinostomy (DCR) – to identify the six anatomical landmark structures of the nose and patency of the ostium. For a minor procedure, retrieval of the retracted silicone intubation tube (n = 3) was attempted using this endoscope. For therapeutic purposes, endoscope-assisted probing in congenital nasolacrimal duct obstruction (CNLDO) patients (n = 6) and endoscope-assisted lacrimal intubation were attempted in cases of failed DCR (n = 7). Diagnostic endoscopy performed in the outpatient department (OPD) and operating room (OR) in preoperative and postoperative DCR patients was almost 80% (n = 25) and 90% (n = 20) successful, respectively. In the remaining patients, owing to deviated nasal septum (DNS) and hypertrophied turbinates, the endoscopy was partially successful or unsuccessful. The minor procedure performed in the OPD group was 100% (n = 3) successful. The therapeutic procedures performed in OR endoscope-assisted probing in CNLDO and endoscope-assisted lacrimal intubation in failed DCR were ~ 33% (n = 2) and ~ 15% (n = 1) successful, respectively. The USB endoscope is more economical, portable, and easy to handle; hence, it is a more convenient alternative to the standard nasal endoscope for diagnostic purposes in pre- and postoperative cases of DCR and is very useful for office/minor procedures; however, its use is limited for therapeutic purposes.